(untitled) (Journal of Educational Sciences, 2018)
Processes of globalization of world development influence not only to expansion of the international integration, and also on personality development. The problem of the theory of personality becomes a significant factor creating conditions for economic and social development of the country.The theory of personality develops primarily within the social and human sciences. At the beginning of the development of human society, the theory of personality was discussed in the philosophical sciences.In this article, personality is defined as an object of social and human sciences. The subject of the article are some more interesting ideas concerning the theory of personality as ISSN 2520-2634 Journal of Educational Sciences. №2 (55). 2018 5 Паридинова Б. a philosophical, pedagogical and socio-psychological concept.The aim is to research the evolution of personality theory in identifying its fundamental principles. Considered the views and their most interesting ideas basic representatives of philosophy, pedagogy, psychology.The results obtained will be used in the activity of the higher school to form a culture of teachers and students in personal-oriented learning. Methodological basis of the research was a system of principles, methods for studying the general patterns of personality as a philosophical, pedagogical and social-psychological concept. In particular, dialectical method of cognition allowed us to consider the problemtheory of personality in different levels. In the paper the concepts of the theory of the personality of authors of foreign countries were analyzed, problems of spirituality, morality, and socialization of the individual were examined. Particular attention was paid to the problem of the teacher’s personality in the context of personal-oriented learning. Results can be useful in designing and understanding educational work of universities. Key words: personality, concept, teacher, personality-oriented learning, humanistic psychology.